2017
DOI: 10.1080/15459624.2017.1334904
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of firefighter personal protective equipment and skin and the effectiveness of decontamination procedures

Abstract: Firefighters' skin may be exposed to chemicals via permeation/penetration of combustion byproducts through or around personal protective equipment (PPE) or from the cross-transfer of contaminants on PPE to the skin. Additionally, volatile contaminants can evaporate from PPE following a response and be inhaled by firefighters. Using polycyclic aromatic hydrocarbons (PAHs) and volatile organic compounds (VOCs) as respective markers for non-volatile and volatile substances, we investigated the contamination of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
170
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(176 citation statements)
references
References 34 publications
(41 reference statements)
1
170
0
5
Order By: Relevance
“…While firefighters' lungs may be protected by SCBA, some airborne chemicals could penetrate or permeate the turnout gear and be absorbed through skin. [31,36] These results, as well as the area air concentrations measured inside the structure during the fire, are also important for understanding the potential risks to trapped occupants or firefighters who run out of air or otherwise remove SCBA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While firefighters' lungs may be protected by SCBA, some airborne chemicals could penetrate or permeate the turnout gear and be absorbed through skin. [31,36] These results, as well as the area air concentrations measured inside the structure during the fire, are also important for understanding the potential risks to trapped occupants or firefighters who run out of air or otherwise remove SCBA.…”
Section: Discussionmentioning
confidence: 99%
“…The study design is described in detail elsewhere. [25,30,31] Briefly, using a repeated-measures design, study participants were grouped into 6 crews of 12 firefighters and each crew was deployed to a pair of fire scenarios using 2 different fire attack tactics (order of introduction was balanced). Six fire scenarios were suppressed using an interior attack from the "unburned side" (advancement through the front door to extinguish the fire) and 6 fires were suppressed with transitional attack (water applied into the bedroom fires through an exterior window prior to advancing through the front door to extinguish the fire).…”
Section: Study Population and Controlled Burnsmentioning
confidence: 99%
“…Because the NIOSH study (Daniels, Kubale, et al, 2014) had a large sample and was based in the United States, fire chiefs, firefighters, and policymakers considered it more credible than any of the previous U.S. studies or studies in other countries, where safety standards, construction materials, and other environmental factors can be very different. In addition, NIOSH's experimental studies highlighted exposure pathways that could increase firefighters' risk of cancer, as well as steps that could be implemented to reduce this risk (e.g., Fent, Evans, and Couch, 2010;Fent, Eisenberg, Evans, et al, 2013;Fent, Eisenberg, Snawder, et al, 2014;Fent, Evans, Booher, et al, 2015;Fent, Alexander, et al, 2017). Moreover, those familiar with the industry described a cultural change following NIOSH's work: Where a dirty uniform had earlier been seen as a "badge of courage" or evidence of a positive marker that one was "a real firefighter," this was no longer a widely held belief after the publicizing of the NIOSH results.…”
Section: Approach For Estimating the Economic Benefit Of Firefightingmentioning
confidence: 99%
“…One recent NIOSH study showed a 54-percent reduction in PAH exposure to neck skin by using cleansing wipes and an 85-percent reduction in PAH surface contamination from on-scene wet decontamination by using dish soap (Fent, Alexander, et al, 2017). However, there have been no systematic attempts to estimate the overall effect.…”
Section: : Estimate the Reduction In Exposurementioning
confidence: 99%
See 1 more Smart Citation